Od niewolnika po elektroniczną osobę prawną, czyli rozważania na temat podmiotowości prawnej dla AI - Królikiewicz, Oliwia (PRAWO i WIĘŹ, 2025)
The impressive development of new technology in recent years and the creation of machines equipped with artificial intelligence systems that are used in an increasing range of tasks required us, to the discussion of the development of artificial intelligence in relation to its responsibility and legal subjectivity. The aim of this article is to compare concepts regarding a legal entity for artificial intelligent agents based on Polish law and EU law. The research activity adopted in the article is supported by a theoretical method that brings together the professional literature and practitioners who use control over technology, including artificial intelligence, on a daily basis. Additionally, the article is supplemented by a dogmatic and legal analysis of the provisions of the Polish Civil Code, the Animal Protection Act and soft law instruments.